Implementation of the String Matching Method on Anggah-Ungguhing Balinese Language Dictionary - Wirawan, I Made Agus; Paryatna, Ida Bagus Made Ludy (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Although the learning media of the Anggah Ungguhing Balinese language has been done anytime and anywhere through a mobile application, this application has several obstacles. In detail, the contributions of this study are: 1) to develop a dictionary application that can be used in offline mode, so that it can be used anytime and anywhere. 2) to apply the string matching method to word search correction in the translator process so that the user gets the correct word from the type of keyword. 3) to develop a new vocabulary sending feature used for users to take part in managing the Anggah Ungguhing Balinese language. 4) to describe students’ learning responses in Anggah Ungguhing Balinese language using mobile application. Positive findings/innovations targeted at this study that support the development of science, technology, and social culture are as follows. 1) the availability of database update features for Anggah Ungguhing Balinese language that can be used for offline mode. 2) the availability of correction features using the string matching method for word search correction in the translator process in the dictionary application. 3) the availability of a new vocabulary delivery feature is used for users to take part in managing the vocabulary of Anggah Ungguhing Balinese language. 4) the students' responses to the Anggah Ungguhing Balinese language have been described based on mobile application in the learning process with an excellent range.